2015
DOI: 10.1021/jf503366c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenolic Compounds in Petals of Nasturtium Flowers (Tropaeolum majus) by High-Performance Liquid Chromatography Coupled to Mass Spectrometry and Determination of Oxygen Radical Absorbance Capacity (ORAC)

Abstract: The contents and profile of polyphenols were analyzed in edible petals of nasturtium flowers (Tropaeolum majus) of three colors, and their oxygen radical absorbance capacities (ORAC) were compared. Three primary anthocyanins (ACNs) and 15 non-ACN phenolic compounds including hydroxycinammic acids (HCAs) and flavonoids (myricetin, quercetin, and kaempferol derivatives) were detected. Anthocyanin concentration was within 31.9 ± 21.7 and 114.5 ± 2.3 mg cyanidin-3-glucoside (cy-3-glu)/100 g fresh weight (FW) in ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 43 publications
4
29
2
1
Order By: Relevance
“…As can be seen in Table 5, the cultivated species (D. × hortorum) of cherry colour showed the highest concentration of TAn (14.74, 12.03 and 11.97 mg of cyanidin-3-glucoside 100 g -1 FW). These results were lower than those reported by Garzón et al (2015) in orange and red flowers of Tropaeolum majus (108.8 and 168.0 mg of cyanidin-3-glucoside 100 g -1 FW, respectively); however, they are similar to those obtained by Benvenuti et al (2016) in red flowers of Dianthus × barbatus, Pelargonium peltatum and Viola × wittrockiana (13.3, 12.5 and 12.4 mg cyanidin-3glucoside 100 g -1 FW, respectively). Lara-Cortés et al.…”
Section: Physicochemical Qualitycontrasting
confidence: 72%
See 1 more Smart Citation
“…As can be seen in Table 5, the cultivated species (D. × hortorum) of cherry colour showed the highest concentration of TAn (14.74, 12.03 and 11.97 mg of cyanidin-3-glucoside 100 g -1 FW). These results were lower than those reported by Garzón et al (2015) in orange and red flowers of Tropaeolum majus (108.8 and 168.0 mg of cyanidin-3-glucoside 100 g -1 FW, respectively); however, they are similar to those obtained by Benvenuti et al (2016) in red flowers of Dianthus × barbatus, Pelargonium peltatum and Viola × wittrockiana (13.3, 12.5 and 12.4 mg cyanidin-3glucoside 100 g -1 FW, respectively). Lara-Cortés et al.…”
Section: Physicochemical Qualitycontrasting
confidence: 72%
“…These results are comparable to those reported in edible flowers of Capparis spinosa and Hedysarum coronarium (5.8 and 8.0 mg QE g -1 of dry extract, respectively), but lower than those of Sambucus nigra (23.6 mg QE g -1 dry extract) indicated by Loizzo et al (2016), who also found that routine and quercetin were the main flavonoids. The higher concentration of flavonoids in D. coccinea, whose flowers are orange, confirms that the colour orange is related to the presence of flavonoids (Garzón et al, 2015), as does the yellow colour of the flowers of different edible plants (Liu et al¸ 2016). Similarly, it is important to note that D. coccinea showed a significant increase in the TFl value at the end of the evaluation, which may be associated with the presence of specific flavonoids (quercetin, naringenin, butein and apigenin) in the dahlia petals (Lara-Cortés et al, 2014;Pires et al, 2018), given their ability to eliminate reactive oxygen species as a response to the beginning of the senescence process, as described by Zhao et al (2012) in flowers of three cultivars of Paeonia lactiflora.…”
Section: Physicochemical Qualitymentioning
confidence: 62%
“…Antioxidants were extracted according to Garzón, Manns, Riedl, Schwartz, and Padilla-Zakour (2015) with modifications. To extract the soluble antioxidants (SAOs), the sample flours (0.1 g) were suspended into 2 ml of 50% (v/v) ethanol.…”
Section: Extraction/hydrolysis Proceduresmentioning
confidence: 99%
“…So, oxygen sensing can be applied for cancer diagnosis and the evaluation of a therapeutic effect . Chromatography, electrochemistry, and luminescence methods have all been developed for oxygen monitoring . However, chromatography is not suitable for biosensing and needs complex equipment; a needle microelectrode needs to be inserted into the tumor site in the electrochemistry method, which is invasive, and furthermore, this technique cannot be used for cellular sensing.…”
Section: Methodsmentioning
confidence: 99%